DESIGN OF A DIGITALIZED INDEPENDENT WASTE BANK INFORMATION SYSTEM USING GOOGLE APPS SCRIPT WITH AN INTEGRATED INPUT GATEWAY AND LIVE CALCULATOR - Fery Andika Kurniawan (INKOFAR, 2026)
Conventional waste bank management often faces challenges regarding transaction data recording accuracy, the risk of incorrect resident ID entry, and delays in updating savings balance information. This research aims to design and implement a digitized, web-based independent waste bank information system using Google Apps Script (GAS), Google Sheets as the database, and Bootstrap for the user interface. The design methodology focuses on minimizing human error by implementing a "Resident ID Master Input" feature (Single Input Gate) that integrates and locks transaction data, alongside a "Live Calculator" for real-time Rupiah value simulations based on pricing data from the *Harga_Komoditas* (Commodity Prices) sheet. Testing results demonstrate that the system successfully eliminates ID input errors across transaction modules (Waste Deposit and Cash Withdrawal), presents transaction history in reverse-chronological order (newest first) with precise timestamps, and displays resident financial data instantly without synchronization delays.